Environmental Health Factors Associated with the Incidence of Acute Respiratory Infection in Toddlers - Paneo, Fuji Dayanti; Irwan, Irwan; Jusuf, Muhammad Isman; Kadir, Sunarto; Paneo, Ibrahim (Journal La Medihealtico, 2023)
The purpose of this study was to analyze the environmental health factors associated with the incidence of acute respiratory infections in toddlers at the Bulango Selatan Health Center, Bone Bolango Regency. This type of observational research with a cross sectional study design. The population is households with toddlers in Bulango Selatan District in 2021 as many as 305 households. A sample of 173 households was calculated using the slovin formula and drawn using purposive sampling technique. Univariate analysis in the form of frequency distribution, bivariate analysis was performed using the chi square test. Multivariate analysis was performed by logistic regression test. All data processing and analysis uses SPSS. Based on the findings, it can be concluded that there is a relationship between house ventilation (χ2 count 34.479; ρ value 0.000), house humidity (χ2 count 19.737; ρ value 0.000), house lighting (χ2 count 8.176; ρ value 0.004), house roomization (χ2 count 10.473 ; ρ value 0.001), kitchen conditions (χ2 Count 7.874; ρ value 0.005), residential density (χ2 Count 12.210; ρ value 0.000), and exposure to cigarette smoke (χ2 Count 6.25; ρ value 0.012) with disease incidence acute respiratory infections in toddlers at the Bulango Selatan Health Center. House ventilation is the environmental health factor that is most related to the incidence of acute respiratory infections in toddlers at the Bulango Selatan Health Center, Bone Bolango Regency. Toddlers with inadequate ventilation conditions tend to be 7.3 times more at risk of experiencing ARI compared to toddlers living with adequate ventilation conditions.